Bibliometric analysis of PTEN in neurodevelopment and neurodegeneration - Zhang, Yun; Tan, Ya-ting; Wang, Mei-juan; Li, Lan; Huang, Ju-fang; Wang, Shu-chao (Frontiers in Aging Neuroscience, 2024)
Phosphatase and tensin homologue deleted on chromosome ten (PTEN) was initially recognized as a significant regulator of cancer suppression and could impede cancer cell survival, proliferation, and energy metabolism. PTEN is highly expressed in neurons and performs crucial functions in neurogenesis, synaptogenesis, and neuronal survival. Disruption of PTEN activity may also result in abnormal neuronal function and is associated with various neurological disorders, including stroke, seizures, and autism. Although several studies have shown that PTEN is involved in the development and degenerative processes of the nervous system, there is still a lack of in-depth studies that summarize and analyse patterns of cooperation between authors, institutions, countries, and journals, as well as research hotspots and trends in this important field. To identify and further visualize the cooperation and comprehend the development and trends of PTEN in the nervous system, especially in neural development and neurological diseases, we used a bibliometric analysis to identify relevant publications on this topic. We first found that the number of publications displayed a growing trend with time, but this was not stable. Universities, institutions, and authors from the United States are leading in this area of research. In addition, many cutting-edge research results have been discovered, such as key regulatory molecules and cellular mechanisms of PTEN in the nervous system, which may provide novel intervention targets and precise therapeutic strategies for related pathological injuries and diseases. Finally, the literature published within the last 5 years is discussed to identify future research trends regarding PTEN in the nervous system. Taken together, our findings, analysed using bibliometrics, may reflect research hotspots and trends, providing a reference for studying PTEN in the nervous system, especially in neural development and neurological diseases. These findings can assist new researchers in developing their research interests and gaining basic information. Moreover, our findings also may provide precise clinical guidelines and strategies for treating nervous system injuries and diseases caused by PTEN dysfunction.